1996
DOI: 10.1002/(sici)1097-0231(199612)10:15<1946::aid-rcm774>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency Detection of 66 000 Da Protein Molecules Using a Cryogenic Detector in a Matrix‐assisted Laser Desorption/Ionization Time‐of‐flight Mass Spectrometer

Abstract: We present the first experimental results obtained using a cryogenically-cooled Nb-Al,O,-Nb superconductorinsulator-superconductor (SIS) tunnel junction detector operating at 1.3 K as an ion detector in a time-of-flight mass spectrometer. As opposed to microchannel-plate ion detectors (MCPs) commonly used in such systems, cryogenic detectors such as SIS detectors offer a near 100% detection efficiency for all ions including single, very massive, slow-moving macromolecules. We describe the operating principle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Employing a liquid-He-cooled Sn-based semiconducting tunnel junction detector, Twerenbold et al (1996) demonstrated the concept with lysozyme (m ¼ 14.3 kDa) and other large biomolecules in a TOF-MS measurement. An Nbbased semiconducting tunnel junction detector was utilized almost at the same time by Frank et al (1996) for high-efficiency detection of human serum albumin (m ¼ 66 kDa). Single protein molecules with masses as high as 750 kDa can be detected with a signal-to-noise ratio of S/N & 5/1 (Frank et al, 1999).…”
Section: A Energy-sensitive Detectionmentioning
confidence: 47%
“…Employing a liquid-He-cooled Sn-based semiconducting tunnel junction detector, Twerenbold et al (1996) demonstrated the concept with lysozyme (m ¼ 14.3 kDa) and other large biomolecules in a TOF-MS measurement. An Nbbased semiconducting tunnel junction detector was utilized almost at the same time by Frank et al (1996) for high-efficiency detection of human serum albumin (m ¼ 66 kDa). Single protein molecules with masses as high as 750 kDa can be detected with a signal-to-noise ratio of S/N & 5/1 (Frank et al, 1999).…”
Section: A Energy-sensitive Detectionmentioning
confidence: 47%
“…The resolving power was 14 at 3 keV in this study. This value is better than the resolving power of 2-9 reported until now at higher energies of 20-30 keV [2,3,17,18]. Therefore, we have demonstrated that the infrared-blocking filter is an effective method for obtaining better energy resolution.…”
Section: Article In Pressmentioning
confidence: 99%
“…Recent studies have shown that the kinetic energy resolution of superconducting particle detectors is worse than that expected from X-ray measurements [2,3]. Infrared radiation is one possible source of unexpectedly bad energy resolution in superconducting particle detectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein samples are either in the form of a glycerol droplet deposited onto the sample plate or have been introduced from ambient pressure into the high vacuum of the mass spectrometer via the micronozzle device. The TOF mass spectrometer was equipped with a cryodetector for mass independent high detection sensitivity and molecule energy analyzing capability [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%